Proyecto investigativo apropio mis raíces, ancestralidad en la memoria (2022)
This research monograph is made from a pedagogical research project, based on a socio-critical paradigm, with a qualitative research methodology focused on home-in-house education, which is what allowed me to approach education in search of identity strengthening. of the participants, mostly Afro-descendants, since I as a person identify myself as Afro-descendants, thus in response to my identity, seeking to contribute to the search for the identity of the project participants, showing the threads that led me to find identity frameworks that colonization has tried to erase in its constant struggle to make us believe that we are all mestizos and have no identity beyond the independence wars, with this I resorted to representational shows such as poetry, music, dance, musical instruments and Afro philosophy and theoretical thought, born from the African diaspora.